Synergies or trade-offs? Harvesting insights on policy coherence from an Integrated Policy Synergy for Sustainable Development (IPSSD) tracker / Shirly Siew-Ling Wong, Zheng-Qiang Chu and Yew-Kang Liew - Siew, Shirly Ling Wong; Zheng, Qiang Chu; Yew, Kang Liew (2022)
The study of policy coherence in trade and health has played an important role in providing insight and information about the level of synchronization in trade and health. In the era of globalization, a concern on policy coherence for trade and health has been rising to ensure a sustainable development goal at the national and global level. However, there is a lack of research focusing on empirical testing to examine the policy coherence level in trade and health in a region even within a country. Therefore, an Integrated Policy Synergy for Sustainable Development (iPSSD) tracker is developed to fill the gap. The iPSSD for trade and health is constructed using 5 important variables that have been chosen from the aspect of trade and health. Based on the iPSSD results, a ranking using concordance index is given to the selected countries. Specific interpretations are given to those countries to ensure clear, accurate and reliable results that reflect the current coherence level in each country. The construction of iPSSD for trade and health is significant as it can assist the respective policymakers to develop responsible preventive measures and preparation against the uncertainty of economics in future.